Pendampingan Strategis dalam Penguatan Kapasitas Kelembagaan di Tingkat Daerah - Rowiyani; Khoerul Soleh; Arista Fitri Diana; Alfin Muslikhun; Mukhlidin; Dafiko Fajar Pratama (Lembaga Penelitian dan Pengabdian pada Masyarakat, 2026)
Strengthening the institutional capacity of labor unions has become an urgent need in facing increasingly complex labor dynamics. The Regional Leadership Board of the National Workers Union Federation (DPD FKSPN) of Semarang Regency, as a workers’ advocacy platform, requires a sustainable organizational development strategy to optimize its role. This community service program aims to enhance leadership capacity, improve administrative and financial management systems, and expand organizational partnerships. The implementation method consisted of three stages: preparation, implementation, and reporting. The preparation stage included needs identification and coordination with partners; the implementation stage involved leadership training, administrative and financial mentoring, and facilitation of strategic networking; while the reporting stage consisted of preparing a final report and providing strategic recommendations. The results showed significant improvements in administrative skills, financial transparency, and participant engagement, with 85% of participants reporting high satisfaction with the program. In conclusion, strategic mentoring has proven effective in strengthening the institutional capacity of DPD FKSPN and supporting the sustainability of its role as a workers’ advocacy organization.